Penggunaan Media Sosial untuk Meningkatkan Keuntungan Republic Vespa - Muhammad Marcellino Navis; Yugih Setyanto (Kiwari, 2025)
Social media has become a vital tool for entrepreneurs adapting to the evolving digital landscape. The presence of TikTok has positively impacted many micro, small, and medium enterprises (MSMEs), especially in marketing their products. In the automotive sector, all entrepreneurs share a common goal: increasing profits through sales. This internship report focuses on the use of TikTok as a marketing tool by the @Republicvespa showroom to boost sales. The author, who also acts as the business owner, is responsible for maximizing company profits through effective marketing strategies. Several challenges were encountered during the internship period, and this report highlights how @Republicvespa utilizes TikTok for marketing purposes. The content produced includes short videos and animations promoting Republic Vespa's products. These contents are designed using strategic marketing communication techniques, such as delivering messages about discounts, free shipping offers, and bonus helmets. All promotional content is documented and uploaded to TikTok to inform potential customers of the latest products and attractive deals. Data for this report was collected using participatory observation, unstructured interviews, documentation, and literature studies. The theoretical framework used is New Media Marketing Theory, as TikTok functions as both a marketing platform and a means to enhance business profitability. Media sosial saat ini menjadi alat penting yang digunakan oleh para pelaku wirausaha dalam mengikuti perkembangan era digital. Keberadaan TikTok memberikan dampak positif bagi banyak usaha kecil dan menengah (UMKM), terutama dalam memasarkan produk mereka. Dalam sektor otomotif, para pelaku usaha memiliki tujuan yang sama, yaitu meningkatkan keuntungan melalui penjualan. Laporan magang ini berfokus pada pemanfaatan TikTok sebagai alat pemasaran oleh showroom @Republicvespa untuk mendongkrak penjualan. Peneliti, yang juga bertindak sebagai pemilik usaha, bertanggung jawab untuk memaksimalkan keuntungan perusahaan melalui strategi pemasaran yang efektif. Selama masa magang, peneliti menghadapi beberapa kendala yang dihadapi oleh Republic Vespa, dan laporan ini menyoroti upaya pemasaran melalui platform TikTok. Konten yang dibuat berupa video pendek dan animasi yang menampilkan produk-produk Republic Vespa. Konten tersebut disusun dengan strategi komunikasi pemasaran yang mencakup penyampaian informasi terkait diskon, gratis ongkir, dan bonus helm. Semua informasi tersebut didokumentasikan dan diunggah ke TikTok agar calon konsumen mengetahui promo menarik dan produk terbaru dari Republic Vespa. Pengumpulan data dalam penulisan laporan ini menggunakan metode partisipasi, wawancara tidak terstruktur, dokumentasi, dan studi pustaka. Teori yang digunakan dalam laporan magang ini adalah teori Pemasaran New Media, karena TikTok dimanfaatkan sebagai platform pemasaran sekaligus sarana untuk meningkatkan keuntungan perusahaan.